Policy subjects and policy actors in schools: some necessary but insufficient analyses - Ball, Stephen J.; Maguire, Meg; Braun, Annette; Hoskins, Kate (Discourse (Abingdon, England), 2011)
This paper explores two different ontological positions from which policy in schools and teachers can be viewed. On the one hand, it explores the ways in which policies make up and make possible particular sorts of teacher subjects - as producers and consumers of policy, as readers and writers of policy. On the other, it begins to conceptualise the hermeneutics of policy, that is the ways in which policies in schools are subject to complex processes of interpretation and translation. We suggest that both views are necessary to understand the work of policy and 'policy work' in schools but that neither view is sufficient on its own.